Conjoint Analysis of SMRT- and Illumina-Based RNA-Sequencing Data of Fenneropenaeus chinensis Provides Insight Into Sex-Biased Expression Genes Involved in Sexual Dimorphism - Wang, Qiong; He, Yuying; Li, Jian (Frontiers in Genetics, 2019)
Fenneropenaeus chinensis (F. chinensis) is one of the most commercially important cultured shrimps in China. The adult F. chinensis exhibit sexual dimorphism in growth and body color. In this research, we profiled the whole transcriptome of F. chinensis by using SMRT-based full-length transcriptome sequencing. We further performed Illumina-based short reads RNA-seq on muscle and gonad of two sexes to detect the sex-biased expression genes. In muscle, we observed significantly more female-biased transcripts. With the differentially expressed transcripts (DETs) in muscle, some pathways related to the energy metabolism were enriched, which may be responsible for the difference of growth. We also digged out a pathway named porphyrin and chlorophyll metabolism. It was speculated to relevant to the difference of body color between the two sexes of shrimp. Interestingly, almost all DETs in these pathways were female-biased expression in muscle, which could explain the phenomenon of better growth performance and darker body color in female. In gonad, several pathways involved in reproduction were enriched. For instance, some female-biased DETs participated in the arachidonic acid metabolism, which was reported crucial in female reproduction. In conclusion, our studies identified abundant sex-biased expression transcripts and important pathways involved in sexual dimorphism by using the RNA-seq method. It provided a basis for future researches on the sexual dimorphism of F. chinensis.